Evaluation of Mex A' Mex B Efflux Pump Gene in Pseudomonas aeruginosa Isolated from Milk in Qom Province, Iran - Badi, Alireza; Dirbaziyan, Ashkan; Shakib, Pegah; Morovvati, Abbas; Zargar, Mohsen (Current Nutrition & Food Science, 2025)
BackgroundPseudomonas aeruginosa is an opportunistic pathogen protected from antibiotics' harmful effects by various mechanisms. One of the most important mechanisms is the activation of exudation systems. Therefore, identifying such targets in food contaminating bacteria can help us target them and eliminate bacteria resistant to several drugs, making food safe. Therefore, the present study aimed to trace Mex A and Mex B efflux pump genes in Pseudomonas aeruginosa isolated from dairy products in Qom City, Iran.Methods300 samples of raw milk, 30 samples of pasteurized milk, and 30 samples of local cream were collected. After a 24-hour culture on nutrient agar and blood agar and performing warm staining, confirmatory biochemical tests were performed to identify bacteria. The disk method was used according to CLSI guidelines to determine the antibiotic sensitivity pattern. Then Mex A and Mex B efflux pump genes were detected using specific primers with PCR technique.Results117 strains of Pseudomonas aeruginosa were isolated from 300 raw milk samples, and 7 strains were resistant to ciprofloxacin. Out of 117 Pseudomonas aeruginosa isolates, 51 isolates (43.5%) had Mex A gene and 10 isolates (8.5%) had Mex B gene. Three isolates had both Mex A and Mex B genes. Among the strains with resistance to ciprofloxacin (7 isolates), 4 isolates did not have any of the genes. One isolate had Mex A and Mex B genes; 2 isolates were Mex A positive and Mex B negative, and Mex B positive and Mex A negative isolates were not observed.ConclusionsBased on the results, among the studied isolates, the Mex A gene was more abundant. In addition, no significant relationship was found between the existence of Mex A and Mex B genes and ciprofloxacin resistance.
Keywords: efflux pump